Maturidade organizacional para adoção de um Centro de Serviços Compartilhados (CSC) - Filgueira, Adriano Araujo (2024)
SSCs consolidate activities supporting key business processes into one main operating unit. The implementation of a SSC can bring significant benefits, such as the standardization of processes, optimization of teams, and improvement in internal and external communication. However, the implementation of a SSC is not an easy task and involves several challenges. One of these challenges is the need to measure the degree of maturity of the organization to ensure a successful implementation. The maturity of the organization is related to the moment or stage in which the organization is on the path of organizational development. The purpose of this research was to identify and analyze the degree of maturity of organizations that intend to adopt the SSC as a model in their structures, as well as for those that have already adhered to it, but are in the process of implementation. In order to answer the question of how to measure and diagnose the level of maturity of an economic group to receive a Shared Services Center? With this, the main objective was to propose a measurement instrument aimed at analyzing the degree of organizational maturity of economic groups for the implementation of a SSC that resulted in the specific objectives of analyzing and understanding the institutional stages of the organizations required for the adoption of the SSC, as well as the specific objective of developing an instrument to measure organizational maturity for the groups intending to implement the SSC model. This research was characterized as an exploratory and descriptive field study. This is an empirical research, reinforcing the qualitative methodology. The scale model that best adapted to the present research was the proposed scale based on John Rossiter's paradigm of the C-OAR-SE model method, hierarchized in the form of a checklist.